INOVASI PRODUK MAKANAN DAN MINUMAN UNTUK MENINGKATKAN NILAI BAHAN LOKAL DI SMA 26 KOTA BATAM - Rosie Oktavia Puspita Rini; ilham, Wahyudi; Mulyadi, tirta; Nuryanto, heri (PUSLITABMAS-Politeknik Pariwisata Batamc, 2024)
SMA 26 is one of the state schools in Batam City. Batam 26 High School or known as Smandanam is a superior school which aims to produce a generation of knowledge and superior character. The PKM Team for the Batam Culinary Management Study Program and Tourism Polytechnic through PKM Activities chose SMA 26 as a partner because the school needs to increase self-development through student innovation through local food. Apart from that, its PKM activities are also in line with the Food Technology and Entrepreneurship courses. The selection of products to innovate is based on discussions between partners and their PKM teams. Based on the results of dedication to innovative learning in building student character in elementary schools, it is that in innovative learning teachers must prioritize fun learning to improve innovative learning outcomes and have students who have good character in learning.